Ilustrasi Sebagai Bahasa Komunikasi Audio Visual Film, Televisi Dan Animasi - Thomas Hanandry (Universitas Dinamika, 2019)
Music is one of the important parts, which are related to the development of creative industries in era 4.0, especially film, animation, and television, as well as other industries related to the arts and media in particular. Music is experiencing very rapid development, starting from development through software to creating compositions, as well as arrangements. Music also has a function to be one of the supporting factors in giving impression, language, and also communication tools in the form of audio in film, animation, and television. One important role is to give a discussion about communication to the audience is to make the audience understand the film. The purpose of this study is to provide information through audio and visual communication to the audience, so that understanding the film is not only visual but also in terms of audio visual. The method used in this study is qualitative research from samples taken from film screening conducted at the Stikom Surabaya Institute of Business and Information. This research is expected to be used as a learning media for audio visual communication courses.